Problems of organizing training in graphic disciplines with credit technology of education - Melkozerovа, Людмила (Рroblems of engineering and professional education, 2022)
In the article, the problem of subjects of educational graphics organized in the course of credit technology studies is considered. In solving these problems, the author considers computer learning methods, pedagogical works, and uses information technologies.